Teachers Work Stress and Conflict Dynamics in Islamic Educational Institutions: An Interpretive Qualitative Study at SMK Ma'arif NU 2 Karanglewas - Rahmadini Mulya Aisah; Rizki Rahayu Noviami; Naily Fauziyah; Enika Sari; Dzulfikar Hardiki; Suparjo Suparjo (LPPM Institut Pendidikan Nusantara Global, 2026)
Teacher work stress and conflict dynamics in educational institutions, particularly at SMK Ma'arif NU 2 Karanglewas, are critical issues that affect learning quality. Using an interpretive qualitative approach, this study explores teachers’ experiences related to workload, psychological pressure, and interpersonal conflict through in-depth interviews, observations, and document analysis. The findings show that high curriculum demands, administrative responsibilities, and emotional strain are major sources of stress that influence teacher motivation, performance, and interactions with students. Conflicts between teachers often arising from miscommunication, unequal task distribution, and differing views on student management further deteriorate the work atmosphere. These results highlight the need for systematic stress and conflict management supported by transformational leadership, clear task allocation policies, effective communication procedures, and stress management training. Consistent implementation of these strategies can enhance teacher well-being, improve workplace harmony, and strengthen overall educational quality while fostering a more supportive and sustainable school environment for the entire school community.